2017
DOI: 10.18553/jmcp.2017.23.9.958
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Rivaroxaban, Dabigatran, and Apixaban for Stroke Prevention for Newly Diagnosed and Treatment-Naive Atrial Fibrillation Patients: An Update Using 2013-2014 Data

Abstract: BACKGROUND Few studies have assessed adherence to non-vitamin K antagonist oral anticoagulants (NOACs), especially using contemporary data now that multiple NOACs are available. OBJECTIVE To compare adherence and treatment patterns among NOACs for stroke prevention in patients with nonvalvular atrial fibrillation (NVAF). METHODS Incident and treatment-naive NVAF patients were identified during 2013–2014 from a large claims database in this retrospective cohort study. Patients were included who initiated ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 47 publications
(57 reference statements)
5
73
3
3
Order By: Relevance
“…Our exposure definition required continuous adherence with a small gap window (7-day) to ensure exposure. 33,34 Likewise, the claims database would not include information on when patients acquired prescriptions not paid for by their insurance coverage, such as over-the-counter or sample medications, [35][36][37] but this information is not expected to be imbalanced between treatment groups and would likely not affect the study results. Our results were consistent in direction and magnitude to several sensitivity analyses including use of standardized mortality ratio weighting in place of IPTW, use of a 15-day gap censor criterion, outcome measurement using all primary and secondary diagnoses, and separating verapamil and diltiazem.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our exposure definition required continuous adherence with a small gap window (7-day) to ensure exposure. 33,34 Likewise, the claims database would not include information on when patients acquired prescriptions not paid for by their insurance coverage, such as over-the-counter or sample medications, [35][36][37] but this information is not expected to be imbalanced between treatment groups and would likely not affect the study results. Our results were consistent in direction and magnitude to several sensitivity analyses including use of standardized mortality ratio weighting in place of IPTW, use of a 15-day gap censor criterion, outcome measurement using all primary and secondary diagnoses, and separating verapamil and diltiazem.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Overall 2-year dabigatran persistence was 70.9% (95% confidence interval [CI] 69.6 to 72.2). Persistence probability was lower in the first 6 ). Of 1,305 patients (26.9%) who discontinued dabigatran, adverse events were reported as the reason for discontinuation in 457 (35.0%).…”
mentioning
confidence: 91%
“…1 Although current guidelines recommend long-term oral anticoagulation (OAC) for stroke prevention in AF patients with at least 1 additional stroke risk factor, 2 high rates of OAC discontinuation have posed a barrier to achieving optimal outcomes. Discontinuation has been especially noteworthy in the era before the availability of nonvitamin K antagonist OACs (NOAC) with 1-year discontinuation rates exceeding 50% 3−5 ; and investigations examining persistence or adherence have primarily been based on claims databases, 6,7 national health registers, 8−11 or commercial databases. 12 Although some evidence indicates discontinuation rates may be lower with NOACs versus vitamin K antagonists, 5,7,13 periods of risk and reasons for NOAC discontinuation remain poorly understood.…”
mentioning
confidence: 99%
“…Although it was reported that adherence to dabigatran is poor in patients with NVAF [11], the mean aPTT showed sta- ble prolongation throughout the present study, suggesting that our patients showed good adherence. This finding supports the favorable adherence to dabigatran therapy and good safety profile revealed by a post-marketing survey in Japan [12].…”
Section: Discussionmentioning
confidence: 47%